Tafsir Ayat-ayat Jihad dalam Perspektif Pendidikan dan Dakwah - Abdul Hadi (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2023)
Literal textual knowledge that may emerge while comprehending the Koran can lead up to anarchic, intolerant, and harmful conduct. This article discusses the interpretation of Al-Qur'an Surah Al-Hajj Verses 39-41 from the perspective of da'wah education. The approach employed is comparative analysis (muqarin). The research findings reveal that, according to the Qur'an, war is allowed in order to defend oneself, religion, and nation. However, because of its Islamic origin, it promotes peace above conflict or violence. The Al-Quran also makes it clear that Islamic connections with the outside world are founded on peace. However, under specific situations, Islam permits for combat.